Population dynamics of Bagrada hilaris (Brumeister) on Indian mustard under semi arid conditions of Haryana, India - Bawaskar DM; Sunita Yadav; SP Singh; KM Kumarnag; AV Nadaf (Journal of Oilseed Brassica, 2026)
Population dynamics study of Bagrada hilaris on RH 30 showed that the pest reached its peak populationtwice in the cropping season, once at the seedling stage, and another at the maturity stage on both early, andlate sown crop. The maximum population on early sown crop was observed with its first, and second peakobserved on 48th SW, and 12th SW, respectively. While in the late sown crop the peaks in the pest populationwere noticed on 50th SW, and 17th SW of 2013-14, and 2014-15. The pest population had significant positivecorrelation with maximum temperature, and sun shine hours on both early, and late sown crops. However, thecorrelation with minimum temperature was non-significantly positive in early sown crop compared to significantpositive correlation in late sown crop. Morning, and evening relative humidity showed highly negative significantcorrelation with the pest population. Wind speed had a significant negative effect on painted bug population incrop sown early in the season while the effect was positive, and non-significant in late sown crop. Allweather parameters contributed to B. hilaris population fluctuation to the extent of 66 to 69, and 46 to 86 percent during 2013-14, and 2014-15 respectively.